Tanggung Jawab Perdata Atas Tindak Pidana Yang Dilakukan Anak Dibawah Umur - Ghulam Muhammad (Jurnal Ilmiah Penegakan Hukum, 2014)
Tort ( Onrechtmatigedaat ) as an institution that has been known sincecodefication western civil law Indonesi. based treated in community justicedemands the interpretation of Article 1365 of the Civil Code has beenprogressing later known as broad interpretation. Today's law enforcementagencies through much needed to meet the justice community because of themany cases arising from the behavior that cause harm to people lain.specialy incases where the perpetrator is a minor, who is responsible for a civil manner.Completion law less economically make sense especially when the victims belongto the status of economically disadvantaged and less acquire understanding ofthe law to protect their rights as a result of an unlawful act. Solving one of thevictims' rights be fulfilled by the institution of civil liability insurance butdirectly to the perpetrators of the perpetrator is still possible especially thosebelonging to economically established . The role of the National Commission andthe National Commission of child protection of human rights in cases relatedhighly desirable .